The relationship among academic self-concept, academic self-esteem, and academic achievement - Abd Basith (Konselor, 2021)
This research aims to: 1) identify the levels of academic self-concept and academic self-esteem, 2) analyze the relationship among academic self-concept, academic self-esteem, and academic achievement, and, 3) analyze the mediating effect of academic self-esteem in the relationship between academic self-concept and academic achievement. The research population is 907 students of STKIP Singkawang, and then a sample of 482 students (107 male and 375 female) is taken using a simple random sampling technique. The research instruments are the academic self-concept and the academic self-esteem scales which are obtained from adaptation, and the GPA documentation. The data are analyzed using SPSS with descriptive statistics, correlation, and regression techniques. The results show that the students mostly have a high level of academic self-concept but moderate academic self-esteem level. There is a significant relationship between academic self-concept and self-esteem, but it is not significantly related to academic achievement. Academic self-esteem does not have a mediating effect on the relationship between academic self-concept and academic achievement. Academic self-concept also does not have a direct effect on academic achievement but is a predictor of academic self-esteem.